2016
DOI: 10.1097/tp.0000000000001370
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Predictor of Posttransplant Portal Hypertension in Adult-To-Adult Living Donor Liver Transplantation

Abstract: BackgroundIn adult living donor liver transplantation (ALDLT), graft-to-recipient weight ratio of less than 0.8 is incomplete for predicting portal hypertension (>20 mm Hg) after reperfusion. We aimed to identify preoperative factors contributing to portal venous pressure (PVP) after reperfusion and to predict portal hypertension, focusing on spleen volume-to-graft volume ratio (SVGVR).MethodsIn 73 recipients with ALDLT between 2002 and 2013, first we analyzed survival according to PVP of 20 mm Hg as the thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…However, splenectomy may be less predictable, and it fails to be effective in 10%‐26% of patients . This is due to the fact that their effectiveness depends on splenic size, with those with larger spleens and a higher spleen‐to‐liver ratio more likely to benefit . Furthermore, splenectomy is associated with longer operative time, higher risk of venous thrombosis, higher risk of infection, and higher volume of blood loss .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, splenectomy may be less predictable, and it fails to be effective in 10%‐26% of patients . This is due to the fact that their effectiveness depends on splenic size, with those with larger spleens and a higher spleen‐to‐liver ratio more likely to benefit . Furthermore, splenectomy is associated with longer operative time, higher risk of venous thrombosis, higher risk of infection, and higher volume of blood loss .…”
Section: Discussionmentioning
confidence: 99%
“…(5,(33)(34)(35)(36)(37)(38)(39) This is due to the fact that their effectiveness depends on splenic size, (40) with those with larger spleens and a higher spleen-to-liver ratio more likely to benefit. (41) Furthermore, splenectomy is associated with longer operative time, higher risk of venous thrombosis, higher risk of infection, and higher volume of blood loss. (42) The blood loss in our series was less than that reported in studies where PIM with splenectomy was done.…”
Section: Discussionmentioning
confidence: 99%
“…Posttransplant portal hypertension (PHT) causes critical problems with liver function and graft regeneration after liver transplantation; intraoperative portal venous pressure (PVP) modulation has been performed to reduce PHT. (1)(2)(3)(4)(5)(6) With accumulated evidence, consensus has been reached on the use of PVP modulation to improve graft function and prevent small-for-size syndrome (SFSS). PVP modulation was initially achieved with portocaval shunting; splenectomy is currently the most common procedure for PVP modulation.…”
Section: See Editorial On Page 1506mentioning
confidence: 99%
“…The intrahepatic vascular resistance is related to the size and quality of the graft. The hemodynamic status is related to the spleen volume and the development of collateral vessels [8,19]. Although the GV/SLV and GRWR are generally accepted as important predictors of the adequacy of the post-transplant liver function (GV/SLV ≥ 35%, GRWR ≥ 0.08%) [4,6], we have encountered some patients whose post-transplant course was not good despite meeting these criteria.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, Gyoten et al . revealed that a spleen volume‐to‐graft volume ratio > 0.95 was a good predictor of a high PVP (>20 mmHg) after reperfusion in ALDLT, regardless of the MELD score, Child‐Pugh score, or graft type . However, there are no reports on the relationship between the GV/SV and PVF for recipients, including children.…”
Section: Discussionmentioning
confidence: 99%